Shock Waves Made Simple - C S Kumar , K Takayama and K P J Reddy
The book essentially presents the basic concepts of Shock Wave physics without using complex mathematical theories and attempts to explain the phenomenon of Shock Waves in terms of physical explanations. After laying the foundations for understanding the physics of Shock Wave phenomenon, the book describes the Reddy tube and the procedure for its calibration, ending with a brief description of its recently developed applications. Finally the book summarizes some of the recent applications of Shock Waves.
Keywords: Physics; Shock Waves Made Simple